Comparative analysis of adenovirus and rotavirus gastroenteritis: insights into inflammatory response and temporal variations - Önal, Pınar; Bozaykut, Abdülkadir (Frontiers in Pediatrics, 2025)
BackgroundAcute viral gastroenteritis remains a leading cause of healthcare costs globally, prompting the need for effective yet simple diagnostic strategies. This study aimed to comprehensively examine the demographic, clinical, and seasonal characteristics, hemogram parameters, and C-reactive protein levels in children diagnosed with adenovirus and rotavirus gastroenteritis.MethodsBy conducting a retrospective study, three groups of children diagnosed with gastroenteritis (Rotavirus positive, adenovirus positive, and rota/adenovirus negative group) were compared in terms of demographic, clinical, and laboratory parameters.ResultsAmong 265 children with gastroenteritis, 59.6% were under 36 months, and 36.8% of this group tested positive for rotavirus, while 30% of them tested positive for adenovirus. A statistically significant association was observed between rotavirus gastroenteritis and high neutrophil/lymphocyte value (2.76 ± 1.52) and decreased mean platelet volume (7.47 ± 0.36 fL). Temporal analysis revealed numerical peaks in the adenovirus group in summer and rotavirus in winter; however, these differences were not statistically significant (p = 0.684, 0.851). Unlike rotavirus, our study did not reveal any prominent laboratory marker that serves as a distinctive feature of adenovirus.ConclusionsOur findings suggested that decreased mean platelet volume and high neutrophil/lymphocyte ratio were found statistically significant in rotavirus gastroenteritis, distinguishing it from other causes of acute gastroenteritis.